Produção de nanopartículas magnéticas e aplicação na imobilização da lipase de Geotrichum candidum - Silva, Milena Rocha Lopes Da (2023)
Lipases catalyzes the hydrolysis of triacylglycerols, producing free fatty acids in aqueous media, but they can also catalyze synthesis reactions in media free or with a low amount of water. Its application has high industrial interest, but its use on a large scale has the economic factor as a downside, making it necessary to search for alternatives that aim to overcome this limitation. A strategy to improve the cost/benefit ratio is the use of the enzymatic immobilization technique, which increases the stability of the enzyme in the reaction medium and assists in its recovery, allowing the reuse of the biocatalyst. The use of magnetic iron oxide nanoparticles (SPIONs) as support in immobilization has advantages since SPIONs are easy to obtain, allowing modifications on their surface (functionalization) that help in the immobilization and stabilization of the enzyme for its application, have a high area surface and can be easily separated from the reaction medium by applying a magnetic field. In the present work, the Fe3O4 nanomagnetic support was synthesized, subjected to silica coating (Fe3O4@SiO2), functionalized with amino groups (Fe3O4@SiO2-NH2) and finally activated with glutaraldehyde (Fe3O4@SiO2-CHO) for lipase immobilization produced by submerged fermentation by Geotrichum candidum (GCL), which was compared with three commercial lipases from different sources, Candida rugosa (CRL), Pseudomonas fluorescens (AKL), from porcine pancreas (PPL) also immobilized on the same support. The characterization of SPIONs and their modifications were performed by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and surface area analysis (BET). The biocatalytic properties for the immobilized (derived) GCL were characterized, determining optimal pH and temperature and thermal stability at 40°C. Optimum activity was observed at pH 8 and 40oC, both for free and immobilized enzymes. At 40oC, the half-life (t1/2) of immobilized GCL was 223 min, equivalent to an increase in thermal stability of approximately 5 times when compared to free GCL. The derivative was applied in the synthesis of cetyl acetate wax ester, using a central composite rotational design (CCRD) for the optimization of the reaction. The maximum conversion obtained was 35.56 ± 1.56% m/v for a reaction time of 120 min using a derivative concentration of 8% (m/v) and temperature of 40oC. The derivative retained virtually all of its initial activity after 6 reuse cycles.